1976
DOI: 10.1042/cs0510133
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependence of Maximal Expiratory Flow Rates before and after Bronchodilators in Patients with Obstructive Airways Disease

Abstract: 1.Gas-density-dependence of maximal expiratory flow rats (V max), defined as the ratio of V max. while breathing helium/oxygen (80:20) to V max. while breathing air at the same lung volume, was examined in relation to other measurements of airways obstruction in patients with obstructive airways disease before and after administration of bronchodilators. 2. Seventeen patients showed a 45% or greater increase in specific conductance (sG aw) after bronchodilator therapy (group A) and thirteen patients demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…In normal subjects V max50 breathing He/02 is 40-60% greater than breathing air (Despas et al, 1972;Benatar et al, 1975). In our patients V max50 rose on average only 2% when breathing He/02 (fig 4) compared with 11-13% increases previously found in groups of less severely disabled bronchitics (Despas et al, 1972;Wellman et al, 1976). We have studied (Kanbour et al, 1977) the washout of nitrogen by three vital capacity breaths of He/02 in seven patients whose chronic bronchitis and emphysema were of similar severity to that of the patients in this study.…”
Section: Discussionsupporting
confidence: 46%
“…In normal subjects V max50 breathing He/02 is 40-60% greater than breathing air (Despas et al, 1972;Benatar et al, 1975). In our patients V max50 rose on average only 2% when breathing He/02 (fig 4) compared with 11-13% increases previously found in groups of less severely disabled bronchitics (Despas et al, 1972;Wellman et al, 1976). We have studied (Kanbour et al, 1977) the washout of nitrogen by three vital capacity breaths of He/02 in seven patients whose chronic bronchitis and emphysema were of similar severity to that of the patients in this study.…”
Section: Discussionsupporting
confidence: 46%
“…The proportion of our asthmatic patients with 20% increased flow rates on He/02 breathing was similar to that reported previously in stable asthmatic patients (Chan-Yeung et al, 1976;Wellman et al, 1976). The relation, however, between degree of airflow obstruction and presence of He/02 response was not so evident.…”
Section: Discussionsupporting
confidence: 91%
“…Ingram et al (1977) showed that in normal subjects isoprenaline appears to dilate preferentially small peripheral airways, and work from the same laboratory (Wellman et al, 1976) suggested that the same is true for patients with airflow obstruction, and that the degree of response to bronchodilators correlates with the presence of increased density dependence of flow after bronchodilators. Despite the fact that our patients all exhibited a pronounced bronchodilator response to isoprenaline the degree of increased density dependence of flow after isoprenaline was not significant for Vmax50, suggesting that although isoprenaline may preferentially dilate small airways, it must have a significant effect on large airways as well.…”
Section: Discussionmentioning
confidence: 97%
“…Even in asymptomatic smokers there is sometimes a reduction in density dependence of maximum flow, suggesting a greater relative contribution of viscositydependent flow regimes (presumably in the peripheral airways) to the total pressure drop between alveoli and flow-limiting airways (78). With established COPD, reduction and even loss of density dependence of maximum flow is common (68, 88,288). Overall, preservation of density dependence probably becomes increasingly uncommon as airflow limitation becomes more severe, although density dependence can be preserved even with severe airflow limitation (88,169,200).…”
Section: Normalmentioning
confidence: 99%